Cogeneration Analysis of Krebet Baru II Sugar Factory Milling Capacity - Arif Hidayat; Saptyaji Harnowi (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
Sugar producers can extend their sugar companies by expanding into non-sugar products. A sugarcane-based company that focuses on product diversification is electricity generation from bagasse. As the principal energy source, the cogeneration system progressively creates two distinct forms of energy (mechanical energy and thermal energy). Krebet Baru 2's sugar factory has a capacity of 5,200 TCD. Under some conditions, it can generate up to 1.5 MW of additional Power. This research aims to investigate the link between capacity and cogeneration efficiency. As a result, extra electricity may be generated forever. According to the data, capacity did not influence cogeneration efficiency. Excess Power may be acquired by optimizing steam usage, assessing inefficient energy sources, and utilizing high-pressure steam production facilities.